Reticular organic polymer and preparation method thereof, battery positive electrode and aqueous zinc-organic battery

By using a mesh organic polymer as the positive electrode material of the aqueous zinc-organic battery, it uses its continuous and fast electron delocalization path and stable mesh skeleton structure to solve the problem of degradation in battery capacity and cyclic performance caused by Zn2+ ions, achieving high specific capacity storage and excellent cyclic stability.

CN119875046AActive Publication Date: 2025-04-25TONGJI UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411987949.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

In existing aqueous zinc-organic batteries, the larger ion radius of Zn2+ ions leads to complex solvation structure and high desolvation energy barrier, which reduces the diffusion kinetics of ions and the structural stability of the organic positive electrode, thereby affecting the capacity and cycling performance of the battery.

Method used

Reticular organic polymers are used as the battery positive electrode material, which is prepared by reaction of 2,6-diaminoanthraquinone and 2,4,6-triformyl phthratoplastyol by hydrogen bonding and π-π stacking in N-methylpyrrolidone to form a nanofiber structure with continuous fast electron delocalization pathways and stable reticular frameworks.

Benefits of technology

This mesh organic polymer material can significantly improve the capacity storage and rate performance of the battery, and extend the cycle life of the battery by optimizing structural stability and anti-dissolving properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875046A_ABST
    Figure CN119875046A_ABST
Patent Text Reader

Abstract

The invention provides a reticular organic polymer and a preparation method thereof, a battery positive electrode and an aqueous zinc-organic battery, and belongs to the technical field of chemical power sources. The preparation method of the reticular organic polymer comprises the following steps: dissolving 2, 6-diamino-anthraquinone and 2, 4, 6-triformyl phloroglucinol in N-methyl pyrrolidone (the mass ratio is 1: (0.1-5.9): (10-100)), uniformly mixing, reacting at a preset temperature, filtering, washing, and drying in vacuum to obtain the reticular organic polymer. A battery positive electrode and an aqueous zinc-organic battery are prepared from the reticular organic polymer. In the electrochemical reaction process of the battery, the reticular organic polymer can promote a high-dynamics H < + > coordination redox reaction with ultralow activation energy, so that slow interface charge transfer of Zn < 2 + > ions caused by a high desolvation energy barrier is overcome, and the battery performance is comprehensively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical power sources, and in particular relates to a network organic polymer and a preparation method thereof, a battery positive electrode and an aqueous zinc-organic battery. Background Art

[0002] Aqueous zinc-organic batteries show broad application prospects in the field of large-scale energy storage due to their environmental friendliness, inherent safety, and structural diversity of organic materials. 2+ Ions are the most widely studied charge carriers in Zn-organic batteries, but their larger ionic radius often leads to larger solvation structures and higher desolvation energy barriers, which inevitably reduce the diffusion kinetics of ions and the structural stability of organic cathodes, ultimately leading to a rapid decrease in the capacity and cycle performance of battery devices. + ) charge carriers provide new possibilities for improving the electrochemical performance of batteries. + ions have the smallest ion size and lightest weight, enabling fast reaction kinetics to resolve Zn 2+ The problem of slow charge transfer at the ion interface. In addition, H + Ion coordination can significantly reduce the mass burden and structural expansion of organic cathodes to avoid irreversible structural damage. Therefore, protons are expected to become ideal charge carriers for the development of advanced Zn-organic batteries.

[0003] Despite the multiple advantages of proton storage, it is still necessary to design cathode materials that match it to fully unleash its potential. Organic materials with multiple protonic active sites and a strong skeleton are essential for efficient proton storage. In recent years, various organic cathode materials with different active sites (such as imine, azo, and carbonyl) have been reported. Among them, carbonyl compounds have been widely used due to their high reactivity and H + Carbonyl small molecules have attracted the most attention due to their coordination sensitivity. However, the high solubility of carbonyl small molecules in aqueous electrolytes can cause irreversible capacity loss during battery cycling. In order to overcome this obstacle, researchers often use the method of polymerizing soluble carbonyl monomers to construct stable organic positive electrodes. However, the twisted molecular chains and random cross-linking characteristics of polymers often lead to disordered stacking structures, which reduce the utilization of redox active carbonyl sites and limit the capacity storage of the battery. Therefore, it is urgent to develop organic polymers with abundant protophilic carbonyl active sites, continuous and rapid electron delocalization paths, and stable and ordered topological structures to further improve the specific capacity and cycle life of proton storage. Summary of the invention

[0004] The present invention is made to solve the above problems, and aims to provide a network organic polymer and a preparation method, a battery positive electrode and an aqueous zinc-organic battery.

[0005] The invention provides a method for preparing a network organic polymer, which has the following characteristics and comprises the following steps: dissolving 2,6-diaminoanthraquinone and 2,4,6-triformylphloroglucinol in N-methylpyrrolidone and mixing them uniformly, reacting them at a preset temperature, and then filtering, washing and vacuum drying to obtain the network organic polymer, wherein the mass ratio of 2,6-diaminoanthraquinone, 2,4,6-triformylphloroglucinol and N-methylpyrrolidone is 1:(0.1-5.9):(10-100).

[0006] The method for preparing the network organic polymer provided by the present invention may also have the following characteristics: wherein the preset temperature is 10° C. to 160° C., and the reaction is carried out at the preset temperature for 6 h to 24 h.

[0007] The method for preparing the network organic polymer provided by the present invention may also have the following characteristics: ethanol or deionized water is used for washing, and vacuum drying is performed at 80° C. for 10 h to 12 h.

[0008] The present invention also provides a network organic polymer, which has the following characteristics: it is prepared by the preparation method of the network organic polymer.

[0009] The network organic polymer provided by the present invention may also have the following characteristics: the network organic polymer has abundant protonic carbonyl active sites, continuous and rapid electron delocalization paths and a stable network organic skeleton structure.

[0010] The present invention also provides a battery positive electrode, which has the following characteristics: it is prepared by using the above-mentioned network organic polymer.

[0011] The battery positive electrode provided by the present invention may also have the following characteristics: wherein, the preparation method of the battery positive electrode is as follows: weigh the network organic polymer, acetylene black conductive agent and polytetrafluoroethylene adhesive, add N-methylpyrrolidone and grind evenly to obtain a slurry, then evenly coat the slurry on the current collector, and obtain the battery positive electrode after drying.

[0012] The positive electrode of the battery provided by the present invention may also have the following characteristics: wherein the current collector is one of titanium foil, nickel mesh, titanium mesh, stainless steel mesh or carbon paper.

[0013] The positive electrode of the battery provided by the present invention may also have the following characteristics: wherein the mass ratio of the network organic polymer, the acetylene black conductive agent and the polytetrafluoroethylene binder is 6:3:1.

[0014] The present invention also provides an aqueous zinc-organic battery having the following characteristics, including: a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode is the positive electrode of the battery, the negative electrode is a high-purity commercial zinc foil with a zinc content of ≥ 99.99%, and the electrolyte is Zn(CF 3 SO 3 ) 2 、ZnSO 4 、ZnCl 2 One or more of the aqueous solutions, the concentration of the electrolyte is 1 mol L -1 ~10molL -1 , the diaphragm is filter paper or glass fiber.

[0015] Functions and Effects of the Invention

[0016] The preparation method of the network organic polymer involved in the invention selects 2,6-diaminoanthraquinone and 2,4,6-triformylphloroglucinol as building blocks, and the two are prepared into the network organic polymer through hydrogen bonding and π-π stacking in N-methylpyrrolidone solvent.

[0017] The network organic polymer prepared by the present invention is composed of nanofibers, and the continuous and rapid electron delocalization path can fully expose the built-in protonic carbonyl active sites, which is conducive to the significant improvement of battery capacity and rate performance; the expanded interconnected network structure enhances the anti-dissolution of organic materials in the electrolyte, which is conducive to the improvement of battery cycle life. In addition, during the electrochemical reaction of the battery, the network organic polymer of the present invention can promote the high kinetics of H with ultra-low activation energy. + Coordinate redox reactions to overcome Zn 2+ The slow interfacial charge transfer of ions due to the high desolvation energy barrier is beneficial to the overall improvement of battery performance.

[0018] Therefore, the network organic polymer prepared by the preparation method of the present invention has abundant protonic carbonyl active sites, continuous and rapid electron delocalization paths and a stable network organic skeleton structure, and when the network organic polymer is used as the positive electrode active material of the aqueous zinc-organic battery, it can react with high kinetics of H + The preferential coordination of ions gives the assembled battery excellent capacity storage and rate performance, as well as excellent cycle stability. This work is of great significance for stimulating excellent proton activity in a variety of redox organics to build advanced zinc-organic batteries.

[0019] In addition, the main raw materials used in the present invention are widely available, low-cost and environmentally friendly. The entire system electrode and electrolyte preparation process is carried out at room temperature and pressure, which is simple to operate, safe and pollution-free. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a scanning electron microscope image of the network organic polymer in Example 1 of the present invention;

[0021] Figure 2 is the structural formula of the network organic polymer in Example 1 of the present invention;

[0022] Figure 3 is the energy band gap of the network organic polymer in Example 1 of the present invention;

[0023] Figure 4 is a UV-visible absorption spectrum of the network organic polymer in Example 1 of the present invention measured in an aqueous electrolyte;

[0024] Figure 5 is a scanning electron microscope image of the network organic polymer in Example 2 of the present invention;

[0025] Figure 6 The third embodiment of the present invention is a network organic polymer positive electrode, a zinc foil negative electrode and a Zn(CF 3 SO 3 ) 2 The rate performance diagram of zinc-organic battery assembled with aqueous electrolyte;

[0026] Figure 7 The third embodiment of the present invention is a network organic polymer positive electrode, a zinc foil negative electrode and a Zn(CF 3 SO 3 ) 2 Cycling stability diagram of zinc-organic battery assembled with aqueous electrolyte at current density of 20A / g;

[0027] Figure 8 The comparative example of the present invention is a net-shaped organic polymer positive electrode, a zinc foil negative electrode and a Zn(CF 3 SO 3 ) 2 / acetonitrile electrolyte to obtain the rate performance diagram of zinc-organic battery;

[0028] Fig. 9 The comparative example of the present invention is a net-shaped organic polymer positive electrode, a zinc foil negative electrode and a Zn(CF 3 SO 3 ) 2 / acetonitrile electrolyte to obtain the cycling stability diagram of zinc-organic battery at a current density of 20 A / g. DETAILED DESCRIPTION

[0029] In order to make the technical means, creative features, objectives and effects of the present invention easy to understand, the following examples are combined with the accompanying drawings to specifically describe the network organic polymer and preparation method, battery positive electrode and aqueous zinc-organic battery of the present invention.

[0030] <Example 1>

[0031] Embodiment 1 provides a network organic polymer and a preparation method thereof.

[0032] The preparation method of the network organic polymer in this embodiment comprises the following steps:

[0033] The mass ratio of 2,6-diaminoanthraquinone, 2,4,6-triformylphloroglucinol and N-methylpyrrolidone solvent is 1:0.59:28.8. 2,6-diaminoanthraquinone and 2,4,6-triformylphloroglucinol are dissolved in N-methylpyrrolidone and mixed evenly. The mixture is reacted at 120°C for 12 hours. After filtration and washing with deionized water, the mixture is vacuum dried at 80°C for 12 hours to obtain a network organic polymer.

[0034] The raw materials used in this example are all commercially available reagent grade products.

[0035] Figure 1 This is a scanning electron microscope image of the network organic polymer in Example 1 of the present invention.

[0036] like Figure 1 As shown, the network organic polymer prepared in Example 1 is composed of basic nanofiber structural units.

[0037] Figure 2 is the structural formula of the network organic polymer in Example 1 of the present invention.

[0038] like Figure 2 As shown, in Example 1, due to the electron-pushing effect of the carbonyl group in the 2,4,6-triformylphloroglucinol molecule and the electron-withdrawing effect of the amine group in the 2,6-diaminoanthraquinone molecule, the two monomer molecules are polymerized into a nanofiber organic module connected by -NH- bonds. Subsequently, driven by H bonds and π-π plane stacking, the adjacent nanofiber network further grows longitudinally and self-assembles into a regularly arranged network organic polymer.

[0039] Figure 3 is the energy band gap of the network organic polymer in Example 1 of the present invention.

[0040] like Figure 3 As shown, the network organic polymer prepared in this example has an ultra-low energy band gap of 2.16 eV, which ensures high conductivity and effective charge transfer, and promotes redox reactions with lower kinetic hindrance.

[0041] Figure 4 It is a UV-visible absorption spectrum of the network organic polymer in Example 1 of the present invention measured in an aqueous electrolyte.

[0042] like Figure 4As shown, after the electrolyte soaked in the network organic polymer was tested by UV-visible absorption spectrum, no obvious absorption peak signal was observed, indicating that the structure of the network organic polymer was quite stable during the electrochemical reaction and was insoluble in the electrolyte. The anti-dissolution property of the network organic polymer of this embodiment mainly comes from its stable interconnected network polymer structure.

[0043] <Example 2>

[0044] Embodiment 2 provides a network organic polymer and a preparation method thereof.

[0045] The preparation method of the network organic polymer in this embodiment comprises the following steps:

[0046] The mass ratio of 2,6-diaminoanthraquinone, 2,4,6-triformylphloroglucinol and N-methylpyrrolidone solvent is 1:1:28.8. 2,6-diaminoanthraquinone and 2,4,6-triformylphloroglucinol are dissolved in N-methylpyrrolidone and mixed evenly. The mixture is reacted at 100°C for 12 hours. After filtration and washing with deionized water, the mixture is vacuum dried at 80°C for 12 hours to obtain a network organic polymer.

[0047] The raw materials used in this example are all commercially available reagent grade products.

[0048] Figure 5 This is a scanning electron microscope image of the network organic polymer in Example 2 of the present invention.

[0049] like Figure 5 As shown, the network organic polymer prepared in this embodiment is composed of basic units of nanofiber structure.

[0050] The structural formula of the network organic polymer in the second embodiment is the same as that in the first embodiment.

[0051] <Example 3>

[0052] Embodiment 3 provides a battery positive electrode and an aqueous zinc-organic battery, wherein the battery positive electrode uses the network organic polymer prepared in embodiment 1.

[0053] The preparation method of the positive electrode of the battery is as follows:

[0054] The network organic polymer, acetylene black conductive agent and polytetrafluoroethylene binder prepared in Example 1 were weighed in a mass ratio of 6:3:1, and N-methylpyrrolidone was added to a mortar and evenly ground for 30 minutes to obtain a slurry. The slurry was then evenly coated on a titanium foil current collector with a diameter of 1.2 cm with a blade, and dried in a vacuum oven at 80°C for 12 hours to obtain an electrode sheet to be assembled as a battery positive electrode.

[0055] In this embodiment, the prepared battery positive electrode is further used to assemble an aqueous zinc-organic battery, as follows:

[0056] The prepared battery positive electrode was used as the positive electrode, high-purity commercial zinc foil (zinc content ≥ 99.99%) was used as the negative electrode, and a GE-Whatman glass fiber separator was placed between the positive and negative electrodes. After being arranged, it was placed in a CR2032 button battery shell, and then 3M Zn(CF 3 SO 3 ) 2 The electrolyte is assembled to obtain an aqueous zinc battery.

[0057] The raw materials used in this example are all commercially available reagent grade products.

[0058] In this embodiment, the prepared aqueous zinc-organic battery was also subjected to electrochemical performance tests, including: testing the device energy storage performance by using a CHI660E electrochemical workstation. Cycling and rate performance tests were performed on a LAND CT2001A battery testing system. The voltage window was 0.35–1.75V.

[0059] Figure 6 The third embodiment of the present invention is a network organic polymer positive electrode, a zinc foil negative electrode and a Zn(CF 3 SO 3 ) 2 Rate performance diagram of zinc-organic battery assembled with aqueous electrolyte.

[0060] like Figure 6 As shown in the figure, the specific capacity of the zinc-organic battery prepared in this example is 350 mAh g when charged and discharged at 1 A / g. -1 When charging and discharging at 100A / g, the rate capacity reaches 190mAh g -1 The above shows high specific capacity storage performance.

[0061] Figure 7 The third embodiment of the present invention is a network organic polymer positive electrode, a zinc foil negative electrode and a Zn(CF 3 SO 3 ) 2 Cycling stability diagram of zinc-organic battery assembled with aqueous electrolyte at current density of 20 A / g.

[0062] like Figure 7 As shown, the capacity retention rate of the zinc-organic battery assembled in this embodiment after 60,000 cycles of charge and discharge is 83.3%, which has excellent cycle stability.

[0063] <Comparative Example>

[0064] This comparative example provides a battery positive electrode and an aqueous zinc-organic battery, wherein the battery positive electrode uses the network organic polymer prepared in Example 1.

[0065] In this comparative example, the preparation method of the positive electrode of the battery is as follows:

[0066] The network organic polymer positive electrode, graphite conductive agent and polytetrafluoroethylene binder prepared in Example 1 were weighed in a mass ratio of 6:3:1, and N-methylpyrrolidone was added to a mortar and evenly ground for 30 minutes to obtain a slurry. The slurry was then evenly coated on a titanium foil current collector with a diameter of 1.2 cm with a blade, and dried in a vacuum oven at 80°C for 12 hours to obtain an electrode sheet to be assembled as a battery positive electrode.

[0067] In this comparative example, the prepared battery positive electrode is further used to assemble an aqueous zinc-organic battery, as follows:

[0068] The prepared battery positive electrode was used as the positive electrode, high-purity commercial zinc foil (zinc content ≥ 99.99%) was used as the negative electrode, and a GE-Whatman glass fiber separator was placed between the positive and negative electrodes. After being arranged, it was placed in a CR2032 button battery shell, and 0.5M Zn(CF 3 SO 3 ) 2 / acetonitrile electrolyte, and assembled to obtain a zinc-organic battery.

[0069] In this comparative example, the prepared zinc-organic battery was also subjected to electrochemical performance tests, including: testing the device energy storage performance by a CHI660E electrochemical workstation. Cycling and rate performance tests were performed on a LAND CT2001A battery testing system. The voltage window was 0.35–1.75V.

[0070] Figure 8 The comparative example of the present invention is a net-shaped organic polymer positive electrode, a zinc foil negative electrode and a Zn(CF 3 SO 3 ) 2 / acetonitrile electrolyte to obtain the rate performance diagram of zinc-organic battery.

[0071] like Figure 8 As shown, the specific capacity of the zinc-organic battery prepared in this comparative example is 83 mAh g when charged and discharged at 1 A / g. -1 When charged and discharged at 100A / g, the rate capacity is 19mAh g -1 , showing poor specific capacity storage performance.

[0072] Fig. 9 The comparative example of the present invention is a net-shaped organic polymer positive electrode, a zinc foil negative electrode and a Zn(CF 3 SO3 ) 2 / acetonitrile electrolyte to obtain the cycling stability diagram of zinc-organic battery at a current density of 20 A / g.

[0073] like Fig. 9 As shown, the capacity retention rate of the zinc-organic battery assembled in this comparative example after 10,000 cycles of charge and discharge is 40.1%, and the cycle stability is poor.

[0074] By comparing the performance test results of zinc-organic batteries prepared using different electrolytes in the comparative example and the third embodiment, it can be seen that the network organic polymer positive electrode has a good performance in Zn(CF 3 SO 3 ) 2 / H 2 The cycling stability in the electrolyte of Zn(CF)O (capacity retention rate is 83.3% after 60,000 cycles) is significantly better than that in Zn(CF) 3 SO 3 ) 2 / Cyclic stability in acetonitrile electrolyte (capacity retention rate is 40.1% after 10,000 cycles). 2+ The high ion reaction energy barrier and slow interfacial charge transfer kinetics make it difficult to store Zn in a network organic polymer cathode 2+ ions showed poor cycling stability.

[0075] Functions and Effects of the Embodiments

[0076] According to Example 1 and Example 2, through a method for preparing a network organic polymer of the present invention, 2,6-diaminoanthraquinone and 2,4,6-triformylphloroglucinol are used as building blocks, and the two are prepared in an N-methylpyrrolidone solvent through hydrogen bonding and π-π stacking. The network organic polymer is composed of nanofibers, and the continuous and rapid electron delocalization path can fully expose the built-in protonic carbonyl active sites; the expanded interconnected network structure improves the electron transmission efficiency and enhances the anti-solubility of the organic material in the electrolyte.

[0077] According to Example 3, when the network organic polymer prepared by the present invention is used as the positive electrode active material of the aqueous zinc-organic battery, it can react with high kinetics H + The ions are preferentially coordinated, and the assembled battery has a specific capacity of 350mAh g when charged and discharged at 1A / g. -1 When charging and discharging at 100A / g, the rate capacity reaches 190mAh g -1 The above shows high specific capacity storage performance, and the capacity retention rate after 60,000 cycles of charge and discharge is above 80%, showing high specific capacity, energy density and excellent cycle stability.

[0078] According to the comparative examples, in the electrochemical reaction process of the battery, the network organic polymer of the present invention can promote the high kinetics of H + Coordinate redox reactions to overcome Zn 2+ The slow interfacial charge transfer of ions due to the high desolvation energy barrier is beneficial to the overall improvement of battery performance.

[0079] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a network organic polymer, characterized in that: The following steps are involved: 2,6-diaminoanthraquinone and 2,4,6-triformylphloroglucinol are dissolved in N-methylpyrrolidone and mixed evenly, and reacted at a preset temperature, and then filtered, washed, and vacuum dried to obtain a network organic polymer. The mass ratio of 2,6-diaminoanthraquinone, 2,4,6-triformylphloroglucinol and N-methylpyrrolidone is 1:(0.1-5.9):(10-100).

2. The method for preparing a network organic polymer according to claim 1, characterized in that: in, The preset temperature is 10° C. to 160° C., and the reaction is carried out at the preset temperature for 6 h to 24 h.

3. The method for preparing a network organic polymer according to claim 1 or 2, characterized in that: in, Use ethanol or deionized water for washing. When vacuum drying is performed, vacuum drying is performed at 80°C for 10 to 12 hours.

4. A network organic polymer, characterized in that The network organic polymer is prepared by the method for preparing the network organic polymer according to any one of claims 1 to 3.

5. The network organic polymer according to claim 4, characterized in that: in, The network organic polymer has abundant protonic carbonyl active sites, continuous and rapid electron delocalization paths and a stable network organic skeleton structure.

6. A positive electrode of a battery, characterized in that: It is prepared using the network organic polymer described in claim 4 or 5.

7. The positive electrode of the battery according to claim 6, characterized in that: in, The preparation method of the battery positive electrode is as follows: The network organic polymer, acetylene black conductive agent and polytetrafluoroethylene binder are weighed, N-methylpyrrolidone is added and uniformly ground to obtain slurry, and then the slurry is uniformly coated on the current collector and dried to obtain the battery positive electrode.

8. The positive electrode of the battery according to claim 7, characterized in that: in, The current collector is one of titanium foil, nickel mesh, titanium mesh, stainless steel mesh or carbon paper.

9. The positive electrode of a battery according to claim 7 or 8, characterized in that: in, The mass ratio of the network organic polymer, the acetylene black conductive agent and the polytetrafluoroethylene adhesive is 6:3:

1.

10. An aqueous zinc-organic battery, characterized in that: include: Positive electrode, negative electrode, separator and electrolyte, Wherein, the positive electrode is a positive electrode of a battery as claimed in any one of claims 6 to 9, The negative electrode is a high-purity commercial zinc foil with a zinc content of ≥ 99.99%. The electrolyte is one or more of Zn(CF3SO3)2, ZnSO4, and ZnCl2 aqueous solutions, and the concentration of the electrolyte is 1 mol / L -1 ~10mol L -1 , The diaphragm is filter paper or glass fiber.

Citation Information

Patent Citations

  • Method for improving performance of COFs (Covalent Organic Frameworks) material used as electrode active material

    CN107180968A

  • Quinoquinonyl-based covalent organic framework material as well as preparation method and application thereof

    CN111333852A

  • Preparation method and application of beta-ketoenamine covalent organic framework material

    CN115819758A

  • Covalent organic framework containing anthraquinone structure and application of covalent organic framework in aqueous zinc ion battery

    CN116925308A

  • Organic superstructure material and preparation method thereof, battery positive electrode and aqueous zinc battery

    CN117624517A